Clean Energy in the EAEU in the Context of Sustainable Development: Compliance and Prospects - Sadovnikova, Natalia A.; Abramov, Valery L.; Ogryzov, Andrey A.; Makhova, Olga A. (International Journal of Energy Economics and Policy, 2020)
Clean energy today is in the focus of attention of the global community. The development of this field is vitally important for preserving natural heritage and reducing budget expenditures. The case of the EAEU is very interesting for research, since its member countries rely on conventional energy sources from Russia and Kazakhstan, which are cheaper than the production of clean energy. The authors examined the legislative framework of the EAEU countries and compared it with the 2030 Agenda for Sustainable Development, identifying their similarity. The authors introduced a method for assessing integration tightness, which allowed to divide the EAEU countries into two groups according to the extent of their integration in the EAEU. The other important finding based on a statistical analysis of the countries’ cooperation in the field of clean energy is that the EAEU takes nearly no actions in this direction, therefore, clean energy is not important enough in the EAEU. Another result of the statistical study is the fact that none of the EAEU countries, except Armenia, will achieve the 2030 Agenda’s goals in the field of clean energy. The authors developed the Index of green potential usage and proposed clean energy development strategy for the EAEU. Keywords: Clean energy, EAEU, 2030 Agenda, sustainable development, energy market JEL Classifications: Q01, Q40, F55 DOI: https://doi.org/10.32479/ijeep.9512